Penerapan Model Pembelajaran Numbered Heads Together (NHT) terhadap Hasil Belajar Siswa pada Materi Sistem Ekskresi - Yuliana, Lusia Retno; Susanti, R; Bintari, Siti Harnina (FMIPA UNNES, 2018)
This aims of this research is to determine the application of NHT learning to student learning outcomes on the material of excretion system. The learning outcomes from this research is the result of learning in the affective and cognitive domain. Research with form of Pre-Experimental Design was held at SMPN 9 Semarang with class VIII D and VIII E as a research sample. Affective learning results show that 62,50% of students are in good categories and 29,69% are in very good category. The results of the N-gain test on students cognitive learning outcomes obtained from the posttest showed a gain of 0,61 with the medium improvement category. The final value analysis shows that 100% of students have complete their learning. Relatively, students give positive responses to the learning method that applied. Learning is accomplished with a value 90% on very high implementation criteria. The conclusion of this research is the method of learning using NHT method can improve student learning outcomes in the material excretion system